Encapsulation of enrofloxacin in liposomes I: Preparation and in vitro characterization of LUV - (:unkn) unknown (INFORMA HEALTHCARE, 2004)
Liposomes are effectively used in the treatment of microbial infections. Higher cellular uptake has been reported when antibiotics are encapsulated in liposomes. In this study, enrofloxacin (ENF) was encapsulated in large unilamellar vesicles (LUVs) and the effects of formulation variables on the liposome characteristics were investigated. Liposomes were prepared using dry lipid film method. A number of variables such as molar ratios of phospholipid (DPPC; DL-alpha-phosphatidylcholine dipalmitoyl), cholesterol, ENF and amount of alpha-tocopherol and the volumes of internal (chloroform) and external phases [phosphate buffered saline PBS (pH 7.4)] were studied. In vitro characterization of the liposomes including the encapsulation capacity, size and drug release properties were carried out. Using of this method, spherical LUV liposomes with high drug content could be produced. Particle size of liposomes changed between 3.12 and 4.95 mum. The molar ratios of DPPC, cholesterol and ENF affected the size of the liposome (p < 0.05). The drug encapsulation capacities were high and changed between 37.1% and 79.5%. The highest ENF encapsulation was obtained with the highest cholesterol content. An increase in the drug encapsulation capacity of the liposome was found with increasing molar ratios of DPPC, cholesterol and ENF (p < 0.05). Furthermore, the release of ENF from the liposomes decreased as the molar ratios of DPPC, cholesterol and ENF increased (p < 0.05). In conclusion, a convenient colloidal carrier for the controlled release of ENF can be prepared by changing the formulation parameters of LUVs.
Keywords: enrofloxacin; liposome; LUV; controlled release; drug encapsulation; stability; formulation; DRUG-RELEASE; FORMULATIONS; CHOLESTEROL; STABILITY